A Golden Opportunity: The Gold Rush, Entrepreneurship and Culture - Michael Stuetzer; Abel Brodeur; Martin Obschonka; David Audretsch; Peter J. Rentfrow; Jeff Potter; Samuel D. Gosling (Institute of Labor Economics (IZA), 2021)
We study the origins of entrepreneurship (culture) in the United States. For the analysis we make use of a quasi-natural experiment – the gold rush in the second part of the 19th century. We argue that the presence of gold attracted individuals with entrepreneurial personality traits. Due to a genetic founder effect and the formation of an entrepreneurship culture, we expect gold rush counties to have higher entrepreneurship rates. The analysis shows that gold rush counties indeed have higher entrepreneurship rates from 1910, when records began, until the present as well as a higher prevalence of entrepreneurial traits in the populace.
Keywords: L26; R12; N5; N9; 330; gold rush; entrepreneurship; culture